Urbanization, productivity differences and spatial frictions - Calin Arcalean; Gerhard Glomm; Ioana Cosmina Schiopu (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study decentralized and optimal urbanization in a simple multi-sector model of a rural-urban economy focusing on productivity differences and internal trade frictions. We show that even in the absence of the typical externalities studied in the literature, such as agglomeration, congestion or public goods, the decentralized city size can be either too large or too small relative to that chosen by a planner. In particular, optimal urbanization exceeds decentralized levels when productivity differences in location specific non-traded goods is small, a case typically arising in developed economies. In contrast, developing countries are likely to display overurbanization. A numerical exercise calibrated to Brazilian data suggests that the wedges can be quantitatively important. Urban biased policies - placing a higher weight on the welfare of city dwellers - are closer to optimal policies than decentralized allocations whenever productivity differences in non-traded sectors are either very small or very large. For intermediate productivity differences, the urban bias leads to larger cities even relative to decentralized policies.
Keywords: R12; R13; O18; J61; 330; city size; productivity differences; multi-sector models; trade costs; welfare